In Search of Javanese Language and Culture in Today’s Youths (Indonesian Students’ Context) - Nuning Wahyu Astuti (Journal on Education, 2024)
Globalization and modern technology have greatly affected most aspects of human life. Language and culture are two of the most affected aspects and the age group which is vulnerable to this change is the youngsters. This paper will elaborate the relation of language, culture, and identity through the Hall’s point of view and it will also explain the relation among the three with the Indonesian context, particularly in Javanese. The factors affecting the language shifting usage from Javanese to Indonesians will also be elaborated further. Those factors include sociocultural, socioeconomic, and educational factors. This paper suggests the integration of technology in language learning to enhance the status of the language itself and to improve the students’ interest in studying their local language.